2017
DOI: 10.1038/srep45959
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analyses of differential gene expression in the bursa of Fabricius between Silky Fowl and White Leghorn

Abstract: Hyperpigmentation in Silky Fowl (SF) results in aberrant immune cell development. However, how melanocytes regulate B-cell proliferation in the bursa of Fabricius (BF) is unclear. To resolve this conundrum, we collected BFs from three-week-old SF and White Leghorn (WL) female chickens for RNA sequencing. The BF development was relatively weaker in SF than in WL. The transcriptome analyses identified 4848 differentially expressed genes, 326 long noncoding RNAs (lncRNAs), and 67 microRNAs in the BF of SF. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
(69 reference statements)
2
8
0
Order By: Relevance
“…While in cattle the GC content were 48.79% and 51.38%, respectively ( Fig 3D). The present results that are in accordance with those of previous studies [33][34][35].…”
Section: A Boxplot Of Average Expression Level Histogram Of Lengthssupporting
confidence: 94%
“…While in cattle the GC content were 48.79% and 51.38%, respectively ( Fig 3D). The present results that are in accordance with those of previous studies [33][34][35].…”
Section: A Boxplot Of Average Expression Level Histogram Of Lengthssupporting
confidence: 94%
“…To maximise the co-expression signal, we chose datasets to represent the greatest possible diversity of tissues and organ systems. Not all studies contain links to a publicly archived dataset, such as a study of induced ochratoxicosis in the kidney cortex [ 55 ] and two studies of the bursa of Fabricius [ 56 , 57 ]. Samples containing less than 10 million reads were not used, such as those from a study of the follicular transcriptome throughout the ovulation cycle [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, a novel high-throughput RNA sequencing (RNA-seq) method identified the ASB2 gene as a gene candidate for pectoralis muscle tenderness in broiler chickens [ 6 ]. Moreover, Han et al [ 7 ] using an RNA-seq method concluded that B-cell development could be affected by noncoding RNAs expressed in the bursa of Fabricius in Silky Fowl chicken strain. Han et al [ 8 ] evaluating the hypothalamic transcriptome provided new insight into miRNA functions involved in timing the rapid development of chicken gonads.…”
Section: Introductionmentioning
confidence: 99%